How do preschoolers interact with peers? Characterising child and group behaviour in games with tangible interfaces in school - Barros-Blanco, Beatriz; Triviño-Rodríguez, José Luis; Trella-López, Mónica; Marco Rubio, Javier (Elsevier, 2022)
Learning social skills is an important part of the socialisation process of children, which should occur at school, at home and in any place where children live. There are very few studies on social interaction and collaboration roles with 3–4 year old. In this paper, we aim to understand collaboration in young children to help them develop their social skills and improve their overall development. To get this, we have designed an observational experiment to monitor and characterise group activity and roles, mediated by technology and using data mining techniques. First, we have designed a game as a free-play situation where the conditions require interplay of three children with toys and among interaction among peers. Children interacts with game through tangible toys. The environment collects accurate data on children’s actions automatically and non-intrusively. We also consider other data from direct observation by psychologists and educators. Then, we have organised a study for groups(triads) of 3 to 4-year-old children playing with this game. We analyse data from 81 children (51.9% boys and 48.1% girls) in groups of three randomly selected. The work proposes a set of actions in the game and from them a set of indicators, which are used as intermediate measures of observation to analyse the playing process. Social interaction is characterised in 5 levels: Coordination, Cooperation, Collaboration, Troubled and Unproductive; and five roles: Saboteur, Missing, Explorer, Actor, Collaborator and Director. We found that children interact socially, engage in play, help each other and mostly reach the level of collaboration. There are minority cases of non-cooperation (Troubled or Unproductive), with conflict situations or trial and error solving processes, which cause the task to last a long time before it is finally finished. We have also found that children can adopt different roles in the group. (...)
Keywords: Interacción social; Early years education; Social interaction; Face-to-face collaborative activities; Tangible interfaces; Collaborative games; Data science applications in education; 3–4 years; Triads of children